RETINOBLASTOMA PRESENTING AS METASTASIS - Arif, Muhammad; Iqbal, Zafar; Islam, Zia -ul- (Journal of Ayub Medical College Abbottabad, 2010)
Objective: The purpose of this study was to evaluate the frequency of metastatic retinoblastoma on initial presentation. Design: Prospective study. Place and duration of study: Supra Regional Centre for Retinoblastoma, Department of Ophthalmology, Khyber Teaching Hospital Peshawar Pakistan from 1st July 1999 to 31st January 2003. Methods: Data was collected from 80 registered Retinoblastoma patients admitted and examined under anaesthesia for tumours assessment. Diagnosis was supported with the help of CT scan and confirmed by histopathology of the enucleated specimen for evidence of optic nerve invasion by the tumour. Results: Twenty (25%) patients were presenting as Metastasis on initial presentation. Mean age was 3.5 years, range was 7 months to 12 years. Out of these 20 patients with metastasis, 10 were male and 10 were female. Eighteen (90%) of them were from lower socio-economic group. Conclusion: Failure in early diagnosis of retinoblastoma, advance age and unilateral disease are associated with extraocular spread; this tragic scenario can be prevented best be early detection and prompt treatment plan implementation. Keywords: CT Scan, Optic nerve invasion, Orbital and Lymph node metastasis.